Evaluation of Solutions Containing Fluoride, Sodium Trimetaphosphate, Xylitol, and Erythritol, Alone or in Different Associations, on Dual-Species Biofilms - Zen, Igor [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Martins, Tamires Passadori [UNESP]; de Morais, Leonardo Antônio [UNESP]; Sampaio, Caio [UNESP]; Hosida, Thayse Yumi [UNESP]; Monteiro, Douglas Roberto [UNESP]; Pessan, Juliano Pelim [UNESP] (MDPI, 2023)
Although the association of polyols/polyphosphates/fluoride has been demonstrated to promote remarkable effects on dental enamel, little is known on their combined effects on biofilms. This study assessed the effects of solutions containing fluoride/sodium trimetaphosphate (TMP)/xylitol/erythritol on dual-species biofilms of Streptococcus mutans and Candida albicans. Biofilms were grown in the continuous presence of these actives alone or in different associations. Quantification of viable plate counts, metabolic activity, biofilm biomass, and extracellular matrix components were evaluated. Overall, fluoride and TMP were the main actives that significantly influenced most of the variables analyzed, with a synergistic effect between them for S. mutans CFUs, biofilm biomass, and protein content of the extracellular matrix (p < 0.05). A similar trend was observed for biofilm metabolic activity and carbohydrate concentrations of the extracellular matrix, although without statistical significance. Regarding the polyols, despite their modest effects on most of the parameters analyzed when administered alone, their co-administration with fluoride and TMP led to a greater reduction in S. mutans CFUs and biofilm biomass compared with fluoride alone at the same concentration. It can be concluded that fluoride and TMP act synergistically on important biofilm parameters, and their co-administration with xylitol/erythritol significantly impacts S. mutans CFUs and biomass reduction.